Analysis of online trading transaction (peer to peer) on e-commerce based on Islamic law - Richardy Affan Sojuangon Siregar; Bella Marisela Caroline; Luqman Isyraqi Lazuardi; Tris Renanda; Hersy Ayu Qodrya; Atthiya Prima Sari; Ramadana Arbi (Journal of Islamic Economics Lariba, 2017)
E-commerce lets buyers order things over the Internet via gadgets wherever they are and whenever they want to. The order will be delivered right to the buyer’s doorstep. There are several e-commerce models at the moment. One model is called peer-to-peer model which has been implemented on three largest e-commerce platforms in Indonesia. The validity of e-commerce from Islamic view is studied in order to clear the Muslims doubt regarding transactions made online. After scrutinizing the peer-to-peer model on e-commerce platforms through the lens of sharia, this article argues that there is an Islamic explanation regarding the validity of e-commerce by means of akad Wakalah bil Ujrah, akad Wakalah, and akad As-Salam. Primary data sources are data obtained from direct observation research in salam transactions, wakalah transactions, and wakalah bil Ujrah transactions. Primary data sources are also obtained from online articles written by scholars that can support the authors’ argument in this article. Secondary data sources used for the completion of this article are obtained from The Quran, Hadith, Council of Indonesian Ulama (MUI)’s fatwas, and related journals. After analyzing the process that took place in an e-commerce transaction using the peer-to-peer model, the authors conclude that there is an Islamic explanation regarding the validity of e-commerce based on peer-to-peer model in Indonesia and the validity of e-commerce is proved legal and acceptable in Islam.E-commerce lets buyers order things over the Internet via gadgets wherever they are and whenever they want to. The order will be delivered right to the buyer’s doorstep. There are several e-commerce models at the moment. One model is called peer-to-peer model which has been implemented on three largest e-commerce platforms in Indonesia. The validity of e-commerce from Islamic view is studied in order to clear the Muslims doubt regarding transactions made online. After scrutinizing the peer-to-peer model on e-commerce platforms through the lens of sharia, this article argues that there is an Islamic explanation regarding the validity of e-commerce by means of akad Wakalah bil Ujrah, akad Wakalah, and akad As-Salam. Primary data sources are data obtained from direct observation research in salam transactions, wakalah transactions, and wakalah bil Ujrah transactions. Primary data sources are also obtained from online articles written by scholars that can support the authors’ argument in this article. Secondary data sources used for the completion of this article are obtained from The Quran, Hadith, Council of Indonesian Ulama (MUI)’s fatwas, and related journals. After analyzing the process that took place in an e-commerce transaction using the peer-to-peer model, the authors conclude that there is an Islamic explanation regarding the validity of e-commerce based on peer-to-peer model in Indonesia and the validity of e-commerce is proved legal and acceptable in Islam.